KUALITAS LAYANAN E-BANKING DI ERA E-SERVICE: TRANSFORMASI PENDEKATAN RISET EMPIRIS SERVQUAL, BSQ & E-S-QUAL - Saputro, Edy Purwo (Benefit, 2010)
Electronic service (e-service) via a web channel is one of the options that many companies use to provide service and support to customers. E-service is becoming increasingly important not only in determining the success or failure of electronic commerce, but also in providing consumers with a superior experience with respect to the interactive flow of information. The purpose of this paper is to review research and is to gather conceptual perspectives on the role and nature of e-service, and the e-service experience. Recent advances in technology have created a surge in technology-based self-service or e-service, and there is an increasing recognition of its role in differentiation and customer interfaces. In order to understand e-service experiences it is necessary to go beyond studies of e-service quality dimensions and to also take into account the inherent characteristics of e-service delivery and the factors that differentiate one service experience from another. The paper reviews the factors that impact on the nature of the e-service experience, taking a wider perspective than that adopted by many researcher on e-service when they focus on the identification of the dimensions of e-service quality. In order to manage the e-service experience it is important to develop a clear articulation of the nature, boundaries, components and elements of specific e-service experiences, and to further investigate the interaction between these factors and service quality dimensions.